2017
DOI: 10.1007/s10964-017-0663-y
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Predictors of Intimate Partner Violence Perpetration and Victimization in Latino Emerging Adults

Abstract: Despite the prevalence of intimate partner violence in emerging adulthood, literature focused on this life stage among Latinos remains limited. This longitudinal study examined acculturation; traditional gender role attitudes; use of alcohol, marijuana, and tobacco; and depressive symptoms in 10th grade as predictors of intimate partner violence perpetration and victimization among Latino emerging adults (N = 823; 58% female). Average age of participants was 15.5 years in 10th grade and 22.7 years in emerging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 100 publications
(154 reference statements)
4
30
0
1
Order By: Relevance
“…Participants described the intersection between patriarchal attitudes and TDV, stating that South Asian cultures’ male preference may influence healthy relationship formation. This result adds to past studies of adolescents from different cultural groups showing an association between acceptance of traditional gender norms and TDV perpetration (Grest, Amaro, & Unger, 2017; Reed, Silverman, Raj, Decker, & Miller, 2011; Reyes, Foshee, Niolon, Reidy, & Hall, 2016). Although many cultures have deeply rooted patriarchal beliefs, several studies of South Asian immigrant women have specifically noted that patriarchal attitudes are linked with increased acceptability of DV and decreased help-seeking behaviors among DV survivors (Ahmad et al, 2009; Ahmad, Riaz, Barata, & Stewart, 2004; Dasgupta, 2007).…”
Section: Discussionsupporting
confidence: 75%
“…Participants described the intersection between patriarchal attitudes and TDV, stating that South Asian cultures’ male preference may influence healthy relationship formation. This result adds to past studies of adolescents from different cultural groups showing an association between acceptance of traditional gender norms and TDV perpetration (Grest, Amaro, & Unger, 2017; Reed, Silverman, Raj, Decker, & Miller, 2011; Reyes, Foshee, Niolon, Reidy, & Hall, 2016). Although many cultures have deeply rooted patriarchal beliefs, several studies of South Asian immigrant women have specifically noted that patriarchal attitudes are linked with increased acceptability of DV and decreased help-seeking behaviors among DV survivors (Ahmad et al, 2009; Ahmad, Riaz, Barata, & Stewart, 2004; Dasgupta, 2007).…”
Section: Discussionsupporting
confidence: 75%
“…Only one study, to the authors' knowledge, has found a significant relationship between depression and men's reports of IPV, 27 whereas others have found no such association. 28 Centering mental health within the theoretical framework provides an important mechanism linking food insecurity to IPV.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence rates of physical TDV specifically for Latino/a adolescents are dissimilar as well. Due to differences in sampling methods, rates for Latino/a youth range between 5% and 44% [16][17][18][19][20]. A national study on Latino youth conducted by Cuevas, Sabina, and Bell (2014) found that TDV increases with age (at around 14 years), with boys more likely to experience violence (18.35%) [16].…”
Section: Introductionmentioning
confidence: 99%